2014
DOI: 10.1037/a0036415
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of multisystemic therapy through midlife: A cost–benefit analysis with serious juvenile offenders and their siblings.

Abstract: This study represents the most comprehensive cost-benefit analysis of an MST clinical trial to date and demonstrates that an evidence-based treatment such as MST can produce modest economic benefits well into adulthood. Implications of the authors' findings for policymakers and public service agencies are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 50 publications
(80 reference statements)
0
60
0
Order By: Relevance
“…At 14‐year follow‐up, rearrests decreased by 54% and days incarcerated by 57% (Schaeffer & Borduin, ); and similar outcomes were sustained though a 22‐year follow‐up (Sawyer & Borduin, ). Moreover, long‐term follow‐ups showed that favorable outcomes extended to the siblings of the juvenile offenders in the MST condition and produced considerable cost savings (Dopp, Borduin, Wagner, & Sawyer, ; Klietz, Borduin, & Schaeffer, ; Wagner, Borduin, Sawyer, & Dopp, ).…”
Section: Outcome Researchmentioning
confidence: 99%
“…At 14‐year follow‐up, rearrests decreased by 54% and days incarcerated by 57% (Schaeffer & Borduin, ); and similar outcomes were sustained though a 22‐year follow‐up (Sawyer & Borduin, ). Moreover, long‐term follow‐ups showed that favorable outcomes extended to the siblings of the juvenile offenders in the MST condition and produced considerable cost savings (Dopp, Borduin, Wagner, & Sawyer, ; Klietz, Borduin, & Schaeffer, ; Wagner, Borduin, Sawyer, & Dopp, ).…”
Section: Outcome Researchmentioning
confidence: 99%
“…Similarly the paper by Byford et al (26) showed no significant difference in the cost-effectiveness of family therapy compared to routine care in hospital, but the family-based outpatient treatment had the highest probability of being cost effective when uncertainty was taken into account. Family-based therapy was found to be cost beneficial for studies on juvenile offenders (20,21) and cost effective for conduct disorders (9). It was also found to be cost effective for most of the studies on mental health, psychosomatic, and relational disorders.…”
Section: Is Family Therapy Cost Effective?mentioning
confidence: 98%
“…Most studies undertook a CEA (n = 14) and among those, 1 study additionally carried out a CUA (19). Four studies evaluated the CBA of family-based intervention, 2 studies only carried out a CBA (20,21), while the 2 other studies included both CBA and CEA (9,22).…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Effects were large and significant for violent felonies as well as for non-violent felonies. Dopp et al (2014) extends the evaluation to include behavior of the siblings of the court-involved youth who were originally randomized. and Aggression Replacement Training) was based on risk categories.…”
Section: Multisystemic Therapymentioning
confidence: 99%